The elusive challenge of leadership development at faith‐based institutions. Issue 171 (18th October 2021) - Jun, Alexander; Aronson, Samuel J.
Abstract: This article describes the rationale given by many faith‐based institutions of higher education for creating and promoting leadership programs. A brief overview of the history of faith based educational institutions is followed by an explanation of the motivations of several different schools for creating and funding leadership programs, as well as the limitations of those programs. The article concludes with suggestions for how these programs can benefit more students and the wider community.